Culture and transfection: Two major bottlenecks in understanding Plasmodium vivax biology - Kumari, Sanju; Sinha, Abhinav (Frontiers in Microbiology, 2023)
The long term in vitro culture of Plasmodium falciparum was successfully established by Trager and Jensen in 1976; however it largely remains unachieved for P. vivax. The major obstacle associated with Plasmodium vivax in vitro culture is its predilection for invading younger reticulocytes and the complex remodeling of invaded reticulocytes. There are many factors under exploration for this predilection and host-parasite interactions between merozoites and invaded reticulocytes. These include various factors related to parasite, host and environment such as compromised reticulocyte osmotic stability after invasion, abundance of iron in the reticulocytes which makes them favourable for P. vivax growth and propagation and role of a hypoxic environment in P. vivax in vitro growth. P. vivax blood stage transfection represents another major hurdle towards understanding this parasite’s complex biology. Efforts in making this parasite amenable for molecular investigation by genetic modification are limited. Newer approaches in sustaining a longer in vitro culture and thereby help advancing transfection technologies in P. vivax are urgently needed that can be explored to understand the unique biology of this parasite.